Populism and the consumer society - Çakirdiken, Emre (Teorija in praksa, 2022)
This study considers how today’s growing consumer culture affects political trends in representative democracies. In recent years, a significant populist upsurge has been seen around the world. While political approaches are vital, to properly understand populism it is also necessary to take sociological perspectives into account. The questions considered in the study are therefore examined from both political and sociological perspectives. The results of the study show that today’s increasing consumer culture is paving the way for the rise of populism in representative democracies. Should the consumer culture experience a significant crisis, populism is likely to become stronger through the support provided by abstaining, blank and pragmatist voter
Keywords: Politična kultura; Populizem; potrošniška družba; Potrošnja (ekonomija)